Pengaruh Model Pembelajaran Example Non Examples Terhadap Peningkatan Keterampilan Berargumentasi Siswa Kelas VIII Pada Mata Pelajaran IPS di SMP Negeri 3 Srengat Blitar - Faridatul Azizah; Bagus Setiawan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is motivated by the low enthusiasm and participation of students in social studies learning which is considered boring due to the lack of facilities and less varied learning methods. The purpose of this study was to determine the influence and magnitude of the influence of the Example Non Examples learning model on improving the argumentation skills of grade VIII students at SMP Negeri 3 Srengat. This study used a quantitative approach with a Quasi Experimental Nonequivalent Control Group design. The research sample consisted of 30 control class students and 27 experimental class students selected through purposive sampling techniques. Data were collected through questionnaires and learning outcome tests, then analyzed using the Independent Sample T-Test and Effect Size tests. The results showed that there was a significant influence of the Example Non Examples learning model on improving students' argumentation skills, with a significance value of 0.000 <0.05. Cohen's d test showed a value of 6.140 which indicated a large influence. These findings indicate that the Example Non Examples model is effective in improving students' argumentation skills in social studies subjects, so it can be used as an alternative learning model to create more active and meaningful learning.